Religious Moderation in The Context of Pancasila: A Study of Role and The Impact is Deep Maintaining Social Harmony - Andika Ronggo Gumuruh (Islamika Inside: Jurnal Keislaman dan Humaniora, 2023)
Abstract: This study examines religious moderation in the context of Pancasila. There are two research questions reviewed in this study, what is the role of religious moderation in maintaining social harmony? What is the impact of religious moderation on society? This study is a literature review that uses a type of qualitative research. The sources and types of data in this study are secondary data, especially data from the literature. This study finds findings of the role of religious moderation in maintaining social harmony with an emphasis on its relation to Pancasila values, namely Encouraging Constructive Interreligious Dialogue, Reducing the Potential for Religious Conflict, Building Pluralism Awareness, Strengthening National Unity, while the impact of religious moderation on society is Increasing Interfaith Tolerance. Promoting Diversity and Social Justice, Promoting Social Unity and creating an Environment of Peace and Social Stability.